Evaluating the local economywide impacts of irrigation projects: Feed the future in Tanzania - Filipski, Mateusz J.; Manning, Dale; Taylor, J. Edward; Diao, Xinshen; Pradesha, Angga (International Food Policy Research Institute, 2013)
This paper presents the findings of a local economywide impact evaluation of Feed the Future irrigation projects in the Morogoro region of Tanzania, using a local economy-wide impact evaluation (LEWIE) simulation model. The findings indicate that these irrigation projects can generate important indirect impacts within the region. The structure of local markets, as well as labor and land availability, shapes project spillovers in ways that point to future directions for development assistance in the region.